O espaço da pronúncia nos livros didáticos de inglês como L2 - Santos, Alessandra dos (2014)
This work belongs to the area of English Phonetics and Phonology. Using exploratory research methods, we will attempt to verify the space allotted to the teaching of pronunciation in pre-selected textbooks and if the activities therein are related to the teaching approach used by the book. Based on a list of the most common pronunciation activities, this paper aims to determine which items, segmentals or suprassegmentals, are most emphasized. Finally, it aims to check if the books incorporate the recent body of work, which regards English as a Lingua Franca. It was found that the four books analyzed fit in the communicative teaching proposal. However, on the matter of lingua franca, a lot of aspects are missing when compared to the core proposed by Jenkins (2000).